2012
DOI: 10.4103/0970-9290.99045
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of prevalence of face fractures in southern Brazil

Abstract: Regular publication of epidemiological data is extremely important for the implementation of prevention campaigns and for an increased awareness of the etiology of fractures affecting the face and other anatomic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
7
23
2
2
Order By: Relevance
“…The symphysis and angle were the most common sites of multiple fractures followed by the symphysis and condyle. This finding was similar to other research studies6,7,13. Based on reports from other studies, the mandible angle fracture was the most frequent in cases of single fractures13, especially with assault-related fractures, and the symphysis and angle fractures were most common in multiple fractures5.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The symphysis and angle were the most common sites of multiple fractures followed by the symphysis and condyle. This finding was similar to other research studies6,7,13. Based on reports from other studies, the mandible angle fracture was the most frequent in cases of single fractures13, especially with assault-related fractures, and the symphysis and angle fractures were most common in multiple fractures5.…”
Section: Discussionsupporting
confidence: 94%
“…Bilateral comparison indicated that the left side had a fracture distribution ratio of 72.5% (103/142). Although fracture patterns have not changed recently, compared to previous research studies6, some changes have occurred in the etiologic factors that affect fractures. Most fractures are caused by accidents and alcohol consumption is highly correlated with etiologic factors of mandibular fractures.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[1] Blunt trauma includes road traffic crash (RTC), altercation, industrial/occupational accidents, sports, and falls. [1234] Penetrating injuries are results of gunshots, missiles, stabbing, and explosions. Pathological diseases such as tumors, osteomyelitis, cysts, osteoradionecrosis may also contribute to facial fracture.…”
Section: Introductionmentioning
confidence: 99%